Systematics of Leonidasdeanea, a new subgenus of Wyeomyia (Diptera: Culicidae), with recognition of Wy. luciae as a valid species and synonymy of Wy. surinamensis with Wy. flui - Lourenço-De-Oliveira, Ricardo; Pereira, Glauber Rocha; Neves, Maycon Sabastião Alberto Santos; Santos, Stephani Da Silva; Ribeiro, Paulino Siqueira; Nascimento-Pereira, Agostinho Cardoso; Talaga, Stanislas; Pavan, Márcio Galvão; Sallum, Maria Anice Mureb; Motta, Monique Albuquerque (Zootaxa, 2026)
A new subgenus, Leonidasdeanea, of the genus Wyeomyia Theobald, 1901 is established based on morphological and molecular analyses. It comprises three sibling species: Wyeomyia chalcocephala Dyar & Knab, Wy. flui (Bonne-Wepster & Bonne) and Wy. luciae Senevet, Chabelard & Abonnenc, the last of which is resurrected from synonymy with Wy. chalcocephala. The larva, pupa and adult female and male, including the genitalia, of these three species are redescribed, along with a summary of the systematics, bionomics and distribution of the new subgenus. In addition, Wy. surinamensis Bruijning, 1959 is formally recognized as a junior synonym of Wy. flui.